2019
DOI: 10.1186/s41240-019-0119-2
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of Hizikia fusiforme and Chlorella sp. extracts against lead acetate-induced hepatotoxicity in rats

Abstract: In the present study, the protective effects of Hizikia fusiforme and Chlorella sp. extracts on lead acetate-induced hepatotoxicity were investigated. Hepatic damage was induced in rats by intraperitoneal (i.p.) injection of lead acetate and the protective effects of H. fusiforme (HZK) and Chlorella sp. (CHL) extracts on lead acetate-induced hepatic damage in rat liver were examined. The results revealed significantly increased glutamic oxaloacetate and glutamic pyruvic transaminase levels in the group treated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…The fact that C. vulgaris or S. platensis could ameliorate gamma radiation and chemical toxicantsinduced increase in serum ALT activity points to their possible protective effects on the liver, probably mediated through reducing the level of lipid peroxidation, improving antioxidant defense system and suppressing reactive ROS [30,31]. Previously, Wu et al [32] reported that S. platensis protective effect may be attributed to its ability to scavenge the oxidationinitiating agents produced during the oxidation of proteins and lipids.…”
Section: -Discussionmentioning
confidence: 99%
“…The fact that C. vulgaris or S. platensis could ameliorate gamma radiation and chemical toxicantsinduced increase in serum ALT activity points to their possible protective effects on the liver, probably mediated through reducing the level of lipid peroxidation, improving antioxidant defense system and suppressing reactive ROS [30,31]. Previously, Wu et al [32] reported that S. platensis protective effect may be attributed to its ability to scavenge the oxidationinitiating agents produced during the oxidation of proteins and lipids.…”
Section: -Discussionmentioning
confidence: 99%
“…In many studies, the anti-inflammatory activity of S. fusiforme is usually evaluated using cells and animal models in vitro and in vivo. , Fu et al isolated calcium alginate from S. fusiforme (SFCA) and tested its anti-inflammatory activity. The experimental results showed that SFCA promoted cell growth, reduced the influence of inflammatory factors stimulated by particulate matter (PM) on macrophages, and showed a strong antiadhesion activity .…”
Section: Bioactivities Of S Fusiformementioning
confidence: 99%